PENCAPAIAN STANDAR INDONESIAN SUSTAINABLE PALM OIL (ISPO) DALAM PENGELOLAAN PERKEBUNAN KELAPA SAWIT DI KALIMANTAN TIMUR / Achievement of Indonesian Sustainable Palm Oil Standards of Palm Oil Plantation Management in East Borneo Indonesia - Rusli Anwar; Santun RP Sitorus; Anas Miftah Fauzi; nFN Widiatmaka; nFN Machfud (Jurnal Penelitian Tanaman Industri, 2016)
Strong opinions have been expressed toward oil palm plantation industry in Indonesia, and these opinions portray that oil palm plantation development in Indonesia has caused the destruction of the environment. One of the efforts currently undertaken by the Indonesian government to ensure the sustainability of the palm oil industry is establishing sustainability standard called the Indonesian Sustainable Palm Oil (ISPO) which is mandatory. ISPO is "guidance" for sustainable oil palm development as well as a commitment based on the laws and regulations aplication of some licenses in Indonesia. The purpose of this study was to determine the capability of oil palm plantation companies in the regional to meet the standards of the Indonesian Sustainable Palm Oil (ISPO) and to identify the problems faced in achieving these standards. This research was conducted in East Kalimantan province on the period June 2012-May 2013. Evaluation of the capability of the companies to achieve the ISPO standards was performed by the audit method, assessment results of all parameters that had been established in accordance with the Principles, Criteria and Indicators in the provision of ISPO which were assessed in a percent unit. The research results showed that the capability of the plantation companies in East Kalimantan in meeting the ISPO standards reached 79,14%, and this capability can be improved up to 100% by increasing efforts to comply with the principles, criteria and indicators that are still not in accordance with the provisions of ISPO are as follows: 1). Licence system and plantation management, 2). Aplication guidance cultivation technics and processing palm fruit, 3). Management and monitoring invironment, 4). Resposibility to workers, and 5). Social resposibility and community. The determantion factor performance on ISPO standard is the commitment of plantation company as a business stakeholder that supported by capable human resources to create the sustainable plantation development and also the goverment action in charge as the regulator in supervising the policy that has been set. Socialization and training about principles and criteria ISPO standard to plantation company needs soon and more intensively done by the government association with ISPO commission to accelerate the application of the ISPO. Socialization and training also are required in order to overcome the constraints in attainment of principles and criteria of the Indonesian Sustainable Palm Oil standard, because of the mentioned efforts are the part of success factors to apply the ISPO.Keyword: ISPO, Management, Palm Oil, Plantations, Sustainable.